Kiprah Guru PAI Dalam Mengembangkan Metode Pembelajaran di Era New Normal - Mohamad Aso Samsudin; Hasanah Hasanah (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2022)
This study aims to determine the PAI learning method that was developed during the new normal era. In addition, it also aims to determine the procedures for PAI teachers in developing learning methods. The research selected in this study used qualitative methods. So that the data collection were done by means of documentation studies, interviews, and field observations. Data analysis in this research uses reduction, presentation, and conclusion of research results. The findings of the research are learning methods developed through the integration of various learning methods, firstly, the integrated investigative group method with mixed methods; second, the online method is integrated with the blended learning method; third, the offline method is integrated with the inquiry method. While the procedure for developing PAI learning methods is carried out by means of identification, development and evaluation.